Hydrothermal Synthesis of Pt-, Fe-, and Zn-doped SnO2 Nanospheres and Carbon Monoxide Sensing Properties. (27th August 2013) - Chen, Weigen; Zhou, Qu; Peng, Shudi
Abstract : Pure and M-doped (M = Pt, Fe, and Zn) SnO2 nanospheres were successfully synthesized via a simple and facile hydrothermal method and characterized by X-ray powder diffraction, field-emission scanning electron microscopy, and energy dispersive spectroscopy. Chemical gas sensors were fabricated based on the as-synthesized nanostructures, and carbon monoxide sensing properties were systematically measured. Compared to pure, Fe-, and Zn-doped SnO2 nanospheres, the Pt-doped SnO2 nanospheres sensor exhibits higher sensitivity, lower operating temperature, more rapid response and recovery, better stability, and excellent selectivity. In addition, a theoretical study based on the first principles calculation was conducted. All results demonstrate the potential of Pt dopant for improving the gas sensing properties of SnO2 -based sensors to carbon monoxide.